PENGARUH GAME ONLINE TERHADAP MOTIVASI BELAJAR SISWA DI SMP IT AZIZIYYAH PEKANBARU - Dewi, Zarima Fatma; Hambali, Hambali; Supentri, Supentri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the initial observation by the researcher, who noticed that many students are engaged in online gaming. The purpose of this study is to determine the influence of online games on students' learning motivation. This research is quantitative in nature with a correlational approach. Sources of information were obtained from various journal findings, articles, and relevant books with titles specified by the author. The research findings conclude that there is an influence of online games on students' learning motivation, and it is negatively impactful. This means that with an increase in online gaming, there is a corresponding decrease in students' learning motivation towards a more diminished state, as seen from the consistency value of the student learning motivation variable (Y) of 28.888 and the regression coefficient of online games (X) at -0.455. This indicates that an increase of 1 unit in online gaming results in a decrease in students' learning motivation by 11.6%. The negative coefficient indicates that online games (X) have a negative influence on students' learning motivation (Y). Furthermore, the calculated F-value is greater than the critical F-value (7.460 > 3.159), thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha), indicating that online games significantly affect students' learning motivation at SMP IT Aziziyyah Pekanbaru.